UNDERSTANDING AND ADDRESSING SEXUAL DEVIANCE: A COMPARATIVE ANALYSIS OF SEXUAL KNOWLEDGE AND BEHAVIOR AMONG TEENAGERS IN SUB URBAN PUBLIC AND RELIGIOUS SCHOOLS - Desky, Ahmed Fernanda (Jurnal Sosiologi Reflektif, 2023)
Several studies indicate that insufficient education on sexual matters in schools is a contributing factor to the engagement of teenagers in sexual deviant behaviors. Another contributing factor to sexual deviance in teenagers is their experience as victims of sexual abuse, parental violence, and coming from broken homes. These factors might promote the development of sexual dysfunction, particularly in suburban regions. The objective of this study is to provide a detailed account of the sexual knowledge and sexual behavior of teenagers attending schools in suburban settings. The researcher selected two schools in Deli Serdang Regency, one being a public school and the other a religious school, both with distinct educational system histories. This research methodology employs a quantitative study design utilizing a survey-based technique. The public school sample consisted of 74 respondents, whereas the religious school sample consisted of 91 respondents. The research data were gathered by a questionnaire and analyzed using the SPSS version 22 software. The findings demonstrated that sexual education in religious schools can significantly mitigate the occurrence of sexual aberrations in comparison to public schools. Meanwhile, teenagers attending public schools view engaging in physical touch while dating as a favorable activity. This contrasts with teenagers attending religious schools, where the emphasis is on instilling stronger religious ideals in order to restrict romantic relationships during adolescence.Beberapa penelitian menyebutkan bahwa kurangnya pengetahuan tentang seks di sekolah menjadi salah satu sebab remaja melakukan penyimpangan seksual. Faktor lain yang memiliki korelasi dengan penyimpangann seksual adalah para remaja tersebut merupakan korban kekerasan seksual, kekerasan orang tua, dan latar belakang dari keluarga broken home yang kemudian memicu munculnya disfungsi seksual di wilayah sub urban. Penelitian ini bertujuan untuk mendeskripsikan bagaimana pengetahuan seks dan perilaku seksual remaja di sekolah yang terletak di wilayah sub urban. Peneliti memilih dua sekolah dengan latar belakang sistem pendidikan yang berbeda, yaitu sekolah umum dan sekolah agama di Kabupaten Deli, Serdang. Metode penelitian ini menggunakan penelitian kuantitatif dengan pendekatan survey. Jumlah sampel sekolah umum sebanyak 74 responden, dan sampel sekolah agama sebanyak 91 responden. Data penelitian dikumpulkan menggunakan angket, dan diolah menggunakan program SPSS versi 22. Hasil penelitian menunjukkan bahwa pengetahuan tentang seks di sekolah agama secara efektif dapat mencegah munculnya penyimpangan seks dibandingkan dengan sekolah umum. Sedangkan remaja di sekolah umum menganggap pacaran dengan melakukan kontak fisik merupakan suatu aktivitas positif. Hal ini berbeda dengan remaja di sekolah agama yang lebih menanamkan nilai-nilai agama untuk membatasi hubungan berpacaran di usia remaja.